EVALUASI KAPASITAS SISWA DALAM KESIAPSIAGAAN BENCANA GEMPA BUMI DAN TSUNAMI DI SMA N 2 PARIAMAN - Mimi Septia Ningsih; Iswandi u (JURNAL BUANA, 2020)
This research aims to determine the capacity of students in earthquake and tsunami disaster preparedness in SMA N 2 Pariaman. This study uses a quantitative descriptive approach. Data on student capacity in earthquake and tsunami disaster preparedness was obtained through an instrument in the form of a questionnaire. The sample of this research were 90 students of Pariaman 2 N High School. Based on the results of the study, it was found that the capacity of students in the parameters of the rules and institutional disaster management was in the moderate category (56.82%). Early warning and disaster risk assessment are in the moderate category (55.22%). Disaster education is in the high category (68.40%). Reduction of basic risk factors is in the moderate category (61%). And for the development of preparedness in all lines are in the high category (65.28%). From the five parameters above, it can be concluded that the capacity of students in earthquake and tsunami disaster preparedness at SMA N 2 Pariaman is in the moderate category (61.35%). Keywords: Capacity, Earthquake, Tsunami